2020
DOI: 10.2147/oajc.s252970
|View full text |Cite
|
Sign up to set email alerts
|

<p>Modern Contraceptive Method Utilization and Associated Factors Among Women of Reproductive Age in Gondar City, Northwest Ethiopia</p>

Abstract: Background: Family planning is defined as the ability of couples or individuals to attain their desired number of children, spacing, and timing of their births with the use of contraceptive methods. Ethiopia is one of the most populated countries in Africa with a high fertility rate, a highly unmet need for family planning, and low contraceptive utilization.Objective: This study aims to assess modern contraceptive method utilization and associated factors among women of reproductive age in Gondar City, Northwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 26 publications
11
23
3
Order By: Relevance
“…Women in the age group of 20-24 years were more likely to use contraceptive methods as compared to the adolescent age group (aged 15-19). This is also consistent with previous studies conducted in Ethiopia as well as other countries in Africa that teenagers were less likely to use contraceptive methods as compared to older women [ 9 11 , 16 ]. This may be due to lack of adolescent friendly sexual and reproductive health services in most parts of the country.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Women in the age group of 20-24 years were more likely to use contraceptive methods as compared to the adolescent age group (aged 15-19). This is also consistent with previous studies conducted in Ethiopia as well as other countries in Africa that teenagers were less likely to use contraceptive methods as compared to older women [ 9 11 , 16 ]. This may be due to lack of adolescent friendly sexual and reproductive health services in most parts of the country.…”
Section: Discussionsupporting
confidence: 92%
“…Having good knowledge on the available contraceptive methods was also found to increase the contraceptive use more than two-fold in this study. This finding has also been reported in previous studies conducted in Gondar, Ethiopia [ 9 ], Southern, Ethiopia [ 11 ], and Tanzania [ 16 ]. This has a programmatic implication of strengthening the behavioral change interventions at the facility as well as at the household levels.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study among students who did not use family planning during the sexual debut, the reason for not used contraception was didn't think of protection (17.8%), didn't mind getting pregnant (17.5%), didn't know what to use (13.8%), had no reason (11.3%) and didn't like contraception (10.8%). In contrast, other studies show different reasons for not using family planning services for 87.1% of the participants was fear of being detected and 59.7% reported that they disliked the judgmental attitude of health workers [15,16]. This indicated there are misconceptions and knowledge gaps.…”
Section: Discussionmentioning
confidence: 89%